Fibulin-3 fragments are prognostic biomarkers of osteoarthritis incidence in overweight and obese women. Issue 4 (April 2016) - Runhaar, J.; Sanchez, C.; Taralla, S.; Henrotin, Y.; Bierma-Zeinstra, S.M.A.
Summary: Objective: To determine the association between three fibulin-3 peptides and the incidence of radiographic and clinical knee osteoarthritis (OA). Design: Women between 50 and 60 years, with a BMI ≥27 kg/m 2, free of knee OA, were recruited. Using binary logistic regression, the association between baseline concentration of serum fibulin (Fib)3-1, Fib3-2 and Fib3-3 and incidence of clinical and radiographic knee OA after 30 months of follow-up was evaluated. Results: Baseline and follow-up measurements were available for 241 women with a mean age of 55.9 ± 3.2 years and mean BMI of 31.7 ± 3.6 kg/m 2 . None of the concentrations of the three Fib3 epitopes were associated with the incidence of medial or lateral joint space narrowing (JSN) ≥1.0 mm or the incidence of Kellgren & Lawrence (K&L) grade ≥2 after 30 months. All three Fib3 epitopes were associated with the incidence of the clinical and radiographic ACR-criteria and Fib3-1 and Fib3-3 also with chronic pain at follow-up. When adjusted for the other Fib3 peptide concentrations, only Fib3-1 was significantly associated to the incidence of the American College of Rheumatology (ACR)-criteria (OR 3.2 [1.2–8.7]) and chronic pain at follow-up (OR 3.0 [1.2–7.7]). Conclusions: Baseline fibulin-3 concentrations are associated with the incidence of clinical knee OA among middle-aged overweight and obese women. Therewith, they meet the criteria of a prognostic biomarker according to the BIPED biomarker classification for OA. Further validation of the fibulin-3 epitopes seems warranted in order to better distinguish subgroups of individuals at increased risk for knee OA development.